Evaluation of Potential Factors Affecting Steel Slag Carbonation - Baras, Amer; Li, Jiajie; Ni, Wen; Hussain, Zahid; Hitch, Michael (MDPI AG, 2023)
Steel slag is a solid waste product generated during the carbonation stage of steelmaking. It has high levels of heavy metals and substantial amounts of free calcium and magnesium oxide, making it unsuitable for use as a cement material. Furthermore, the disposal of steel slag in landfills requires many resources and can seriously contaminate the surrounding environment. One method of reducing its negative environmental impact is carbonation, which involves reacting steel slag with carbon dioxide to form stable minerals. However, many parameters influence the carbonation efficiency of steelmaking slag, including temperature, time, particle size, pressure, CO2 concentration, liquid-to-solid ratio, moisture content, humidity, additives, etc. To this end, this paper comprehensively reviews the most important steel slag carbonation-influencing factors. Moreover, it compares the characteristics from two perspectives based on their causes and effects on carbonation. Finally, this article reviews earlier studies to identify the factors that affect steel slag carbonation and the potential of carbonated steel slag as a sustainable construction material. Based on previous research, it systematically examines all the elements for future work that need to be improved.